Sustainable development of urban agglomeration industrial layout based on big data and deep learning - Renzhou Gui; Huilin Zheng; Tongjie Chen; Chuan Pang; Chengkun Liu (Global Journal of Ecology - Peertechz Publications, 2021)
Urban agglomeration is a complex movement system composed of natural environment, social economy and human on the basis of city. At present, many urban agglomerations have a large development gap between cities and lack of overall coordination, and some regions and industries still have homogeneous competition and resource misallocation. This makes the regional development of urban agglomeration unbalanced and difficult to sustainable development. By using deep learning and big data methods, this paper makes an in-depth analysis of the spatial distribution evolution of the number of enterprises and economic scale in urban agglomerations in the Yangtze River Delta region of China, analyzes the mutual influence among urban agglomerations, and discusses the methods of sustainable development.